The influence of copper-cobalt co-doping on optical and electrical properties of nanostructures TiO2 thin films prepared by sol-gel - Toubal, Badreddine; Bensaha, Rabah; Yakuphanoğlu, Fahrettin (Springer, 2017)
In the following undertaking, we have dealt with both the annealing temperature effects and the co-addition of Cu and Co on the structural, optical, and electrical proprieties of TiO2 thin films elaborated by sol-gel dip-coating route. Thermal analysis of obtained xerogels show that crystallization process of TiO(2)and CoTiO3 phase formation occur at lower temperature with (Cu-Co) addition. Transmission electron microscopy micrographs reveal that all TiO2 xerogels present agglomerate nature with the decrease of particle sizes when the Co is doped and (Cu-Co) are co-doped TiO2 powders. The crystalline structure and the functional groups of films were estimated by X-ray diffraction, Raman, and fourier transform infrared spectroscopy analyses. Different structure shapes are observed from atomic force microscopy (100 nm) and scanning electron microscope micrographs between films annealed at 800 A degrees C and those annealed at 1000 A degrees C accompanied by an increment in the particle sizes and surface roughness. The optical reflection attains 90% with more undulations, which are presented in the films annealed at 1000 A degrees C than those annealed at 800 A degrees C. The electrical performance at room temperature of both films annealed, respectively, at 800 and 1000 A degrees C exhibit a similar behavior depicting an ohmic nature. The electrical conductivity (sigma) of films deduced from I-V testing was found for submitting semi-conducting character with the same factor (sigma similar to 10(-12)) with both films that are annealed, respectively, at 800 and 1000 A degrees C. [GRAPHICS] .
Keywords: Sol-gel; TiO2 xerogels; Nanocomposite films; CoTiO3-TiO2 polyhedral structure